O ensino universitário do Curso de Direito: evidenciação ou maquiagem da dupla dimensão ontológica do fenômeno jurídico? - Nascimento, Felipe Azevedo do (2019)
The present paper deals with the subject of teaching about the legal aspects of the Law Course in Higher Education Institutions in Brazil, showing the misalignments and challenges to the formation of university students, starting from the premise - brought by Roberto Lyra Filho in his work What is Right - that, in order to teach the law satisfactorily, one must first understand it properly. In this regard, taking as a theoretical basis the work For an Ontology of Social Being by Geörgy Lukács, the relevance of the present work emerges whose objective is to demonstrate the need to understand the being of the juridical phenomenon by highlighting its dual ontological dimension in capitalism, emphasizing that this double dimension is not taken into account in the teaching process in the Superior Courses of Law. The question that arises is: does university education at the Law Courses in Brazil provide a training that allows its students and graduates to understand this dual ontological dimension of the juridical? We start from the assumption that law is part of the organization of the social life of men, but it can not be considered as a totally autonomous social category, since it derives from the social relations of production and distribution of goods. In this way, it has its positive and necessary side, since it is an essential part of human sociability; on the other hand, it has its negative and contingent side, since it results from a productive system - capitalism - whose end is the profit and exploitation of some men over other men and, in this respect, the Law ends up by serving predominantly, to those who have political, economic, ideological, social, etc. This double dimension of the Law is not demonstrated and / or taken into account in the teaching of Undergraduate Law. Therefore, their graduates have a strong tendency to exercise their legal profession more for their own interests than for the interests and needs of the human being, the collectivity. Our research, because it is of a purely theoretical nature, refers to the presupposition of Lukács' Ontology of Social Being, which is the reference work in this study. However, we also take as bibliographical references the positions of Roberto Lyra Filho, Luís Alberto Warat, Eduardo Bittar and Horácio Wanderlei Rodrigues. These thinkers maintain that, in order to be able to have a legal education in a transformative way, it is fundamental that it should abandon the function of being merely an ideological reproducer of the State, starting to be based on a new creative social imaginary that meets the needs of the population in an egalitarian way, always committed to values that can equalize the differences between classes. As a partial result of the research, from our readings about the authors discussed here, we can infer that there is indeed a double dimension of the legal phenomenon in capitalist society and that this is reflected in the teaching of Law Courses and certainly influences in the formation and of young lawyers. Therefore, in order for a structural change in legal education to take place, it is fundamental that the University Law Courses provide a training that allows academics to understand the ontological dimensions of the juridical, changing the very conception about Law, so that it to be used in the service of a more just and democratic society.